Analisis Kendala Pembelajaran Matematika Berbasis Online (E-Learning) Pada Masa Pandemi COVID-19 - Tri Putri, Soffiani; Dadang Rahman Munandar, (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2021)
Mathematics is an essential subject to study so that it must be pursued in its implementation and possible. The existence of the covid-19 pandemic requires all learning activities to be carried out online. But in practice, online learning experiences several obstacles, especially in learning mathematics. For this reason, the purpose of this study is to describe the constraints in the online-based mathematics learning process (e-learning). This study uses a descriptive method with a qualitative approach. The subjects in this study were students of class VIII SMPN 1 Rawamerta. The research instrument was in the form of a student response questionnaire regarding online-based learning (e-learning), which consisted of seven closed questions and four open questions. Data collection was carried out by distributing the google link form to the student response questionnaire to the research subject. Data analysis was carried out descriptively by testing the validity of the data through triangulation techniques. The results showed that students' obstacles in online-based mathematics learning (e-learning) were technical and personal constraints. Technical constraints are in the form of an unstable internet network, internet quota, and teacher explanations that are not heard clearly. In contrast, unique constraints are the lack of students in understanding the learning material and feeling lazy to take online-based mathematics learning.